The Influence of Integrated Marketing Communication (IMC) on Purchase Decision on Culture Products at Viera Oleh - Oleh in Pekanbaru City - Moniqa, Nadya; Berampu, Lailan Tawila; Wildah, Sri Wahyuni (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2025)
this study aims to find out and analyze how the Influence of Integrated Marketing Communication (IMC) on Purchase Decion on Culture Products in Viera Oleh-Oleh of Pekanbaru City. This study used 125 respondents as samples taken from the purposive sampling technique. The approach used in this study is quantitative by using the Partial Least Square model and SmartPls 4.0 software as tools for this research. The results of this study reveal that there is a significant effect of Advertising on Perceived Quality on Culture Product at Viera Oleh - Oleh Pekanbaru City, there is a significant effect of Sales Promotion on Perceived Quality on Culture Product at Viera Oleh - Oleh Pekanbaru City, there is a significant effect of Public Relations on Perceived Quality on Culture Product at Viera Oleh - Oleh Pekanbaru City, there is a positive and significant effect of Personal Selling on Perceived Quality on Culture Product at Viera Oleh - Oleh Pekanbaru City, there is a significant effect of Direct Marketing on Perceived Quality on Culture Product at Viera Oleh - Oleh Pekanbaru City, there is a significant effect of Perceived Quality on Purchase Decision on Culture Product at Viera Oleh - Oleh Pekanbaru City, there is a significant effect of Integrated Marketing Communication (IMC) on Purchase Decision on Culture Product at Viera Oleh - Oleh Pekanbaru City, there is a significant effect of Integrated Marketing Communication (IMC) on Purchase Decision with Perceived Quality as a intervening variable on Culture Product at Viera Oleh - Oleh Pekanbaru City.